Pengaruh Profitabilitas, Likuiditas dan Hargasaham terhadap Kebijakan Deviden Perusahaan Pertambangan - Irwanda Agusman; Sutia Budi (Indonesian Journal of Economics Application (IJEA), 2020)
The purpose of this study was to determine the development of profitability, liquidity, stock prices and dividend policies, also to determine the effect of Profitability, Liquidity and Share Prices on Dividend Policy in Mining Sector Companies on the Indonesia Stock Exchange in the 2014-2018 period. The research method used is quantitative descriptive. In this study, the authors used the multiple regression method. The results, where the effect of profitability, liquidity and share price on the dividend policy in a simultaneous of 6.298 with the Ftable results obtained at 1.47. This means that the value of F-value > F-table (6.298> 1.47) with a significant 0.003 (sig <0.05) This shows that profitability, liquidity, and stock prices together have a significant effect on dividend policy. With a partial test, it shows a significant value of profitability variable 0.004 where it is smaller than 0.05 so that it can be said profitability variable has a significant effect on dividend policy. The significant value of the liquidity variable 0.087 where this is greater than 0.05, so it can be said that the liquidity variable does not have a significant effect on dividend policy. The significant value of the stock price variable is 0.582, greater than 0.05. We can say that the stock price variable has no significant effect on dividend policy. The coefficient of determination shows that the effect of profitability, liquidity, and Share Price variables on dividend policy of 4.40%, the remaining 5.60% is influenced by factors not entered into this research. This means that simultaneously the effect of profitability, liquidity, and Share Price variables on dividend policy is at a moderate level.